Enhanced detection of terrestrial gamma‐ray flashes by AGILE. Issue 21 (6th November 2015) - Marisaldi, M.; Argan, A.; Ursi, A.; Gjesteland, T.; Fuschino, F.; Labanti, C.; Galli, M.; Tavani, M.; Pittori, C.; Verrecchia, F.; D'Amico, F.; Østgaard, N.; et al.
Abstract: At the end of March 2015 the onboard software configuration of the Astrorivelatore Gamma a Immagini Leggero (AGILE) satellite was modified in order to disable the veto signal of the anticoincidence shield for the minicalorimeter instrument. The motivation for such a change was the understanding that the dead time induced by the anticoincidence prevented the detection of a large fraction of Terrestrial Gamma‐Ray Flashes (TGFs). The configuration change was highly successful resulting in an increase of one order of magnitude in TGF detection rate. As expected, the largest fraction of the new events has short duration (<100 μs), and part of them has simultaneous association with lightning sferics detected by the World Wide Lightning Location Network. The new configuration provides the largest TGF detection rate surface density (TGFs/km 2 /yr) to date, opening prospects for improved correlation studies with lightning and atmospheric parameters on short spatial and temporal scales along the equatorial region. Key Points: Tenfold improvement in TGF detection rate by AGILE is obtained after a major configuration change The sample is dead time‐free, with TGF durations as short as 20 μs The relationship between TGF duration and likelihood of association with lightning is confirmed